2018
DOI: 10.1016/j.ygyno.2018.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Patient inflammatory status and CD4+/CD8+ intraepithelial tumor lymphocyte infiltration are predictors of outcomes in high-grade serous ovarian cancer

Abstract: Systemic inflammation and TILs are early determinants of OS in HGSOC. Other variables such as the quality of debulking surgery and PDL1 also improve survival of patients. Regarding TIL sub-populations, intraepithelial CD4+ cells are associated to an increase in both PFS and OS. We also confirmed previous reports that demonstrate intraepithelial CD8+ cells correlate with an increase on PFS in ovarian cancer. A combined score using systemic inflammation and TILs may be of prognostic value for HGSOC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
76
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 40 publications
(50 reference statements)
11
76
2
1
Order By: Relevance
“…The most abundant type of lymphocyte subset is the T cell. Several studies have shown a positive prognostic impact of a high concentration of tumor-infiltrating T cells in various malignancies, including ovarian cancer [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The most abundant type of lymphocyte subset is the T cell. Several studies have shown a positive prognostic impact of a high concentration of tumor-infiltrating T cells in various malignancies, including ovarian cancer [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several reports indicated that the efficacy of PD-1 inhibitors might be related to peripheral blood lymphocytes. Inflammatory markers such as neutrophil-tolymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and lactate dehydrogenase (LDH) may be potential predictive and prognostic factors related to immunotherapy, as shown in recent studies (33)(34)(35). The NLR/PLR was defined as an absolute neutrophil/platelet count divided by an absolute lymphocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis with almost 4500 patients with mixed or serous histologic subtypes of ovarian cancer showed that intraepithelial CD3+, CD8+, and CD103+ TILs are clearly associated with increased overall survival and disease specific survival, with the location of TILs within the tumour being important for this prognostic effect [ 7 ]. T-cell infiltration has been shown to be subtype dependent in ovarian cancer [ 92 , 93 , 94 ]. Several studies have found that activated CD4+ T or CD8+ T tumour infiltrating lymphocytes are associated with good overall survival in HGSOC [ 93 , 94 , 95 , 96 , 97 ].…”
Section: Tumour Microenvironment (Tme) Of Solid Cancers Including mentioning
confidence: 99%
“…T-cell infiltration has been shown to be subtype dependent in ovarian cancer [ 92 , 93 , 94 ]. Several studies have found that activated CD4+ T or CD8+ T tumour infiltrating lymphocytes are associated with good overall survival in HGSOC [ 93 , 94 , 95 , 96 , 97 ]. Different T-cell infiltration is prognostic for other epithelial ovarian cancer subtypes.…”
Section: Tumour Microenvironment (Tme) Of Solid Cancers Including mentioning
confidence: 99%